Le Programme d’Acquisition d’Aliments (PAA) au Brésil : l’agriculture locale et familiale au cœur de l’action publique en vue de la sécurité alimentaire - Paulo Eduardo Moruzzi Marques; Marcos Freitas Le Moal (VertigO)
This paper presents an analysis of the implementation of the local food purchase Programme (PAA) in rural settlements in Brazil. As a public policy device wich incorporates support to the commercialization of smallholder agriculture and food aid for people in difficulty, the PAA is a significant innovation for food security, in particular by promoting the formation of short circuits nearby.Thus, our study focuses on two areas in the state of São Paulo : on the one hand the Milton Santos settlement is located in the periphery of the second largest metropolitan area in the state, around Campinas, on the other hand, the Antônio Conselheiro and Margarida Alves settlements are in Mirante do Paranapanema township in the region of Pontal do Paranapanema, west of the state, far from major urban centers. For these three settlements, we examined changes in the productive and dietary logic of the families of Small farmers and the beneficiaries of the food distribution.